2016
DOI: 10.1016/j.neuint.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A high fat diet alters metabolic and bioenergetic function in the brain: A magnetic resonance spectroscopy study

Abstract: Diet-induced obesity and associated metabolic effects can lead to neurological dysfunction and increase the risk of developing Alzheimer's disease (AD) and Parkinson's disease (PD). Despite these risks, the effects of a high-fat diet on the central nervous system are not well understood. To better understand the mechanisms underlying the effects of high fat consumption on brain regions affected by AD and PD, we used proton magnetic resonance spectroscopy (1H-MRS) to measure neurochemicals in the hippocampus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…also on midlife intake). Our results point to reduction of fat intake in midlife and are in agreement with studies of Luchsinger et al [27], Laitinen et al [26] and with studies on rodents reported by Kadish et al [28] and Raider et al[29]. We propose only a modest shift in the consumption of fat, from the historical one, which we believe can reduce the AD susceptibility of a population, including also apolipoprotein E epsilon 4 allele carriers.…”
Section: Discussionsupporting
confidence: 93%
“…also on midlife intake). Our results point to reduction of fat intake in midlife and are in agreement with studies of Luchsinger et al [27], Laitinen et al [26] and with studies on rodents reported by Kadish et al [28] and Raider et al[29]. We propose only a modest shift in the consumption of fat, from the historical one, which we believe can reduce the AD susceptibility of a population, including also apolipoprotein E epsilon 4 allele carriers.…”
Section: Discussionsupporting
confidence: 93%
“…This NAA increase may be linked to changes of osmolarity since the concentration of other major osmolites such as taurine and creatine was also observed. In rats under 60% HFD for 5 months, Raider et al (2016) have observed no changes in hippocampal NAA but reduced levels of myo-inositol, compared to controls. Hassan et al (2018) also observed HFDinduced metabolic changes in extracts from the prefrontal cortex, namely, higher relative concentrations of lactate, alanine, taurine, and myo-inositol, and lower GABA levels.…”
Section: Brain Metabolic Profilesmentioning
confidence: 74%
“…This is likely due to the distinct study designs, diet compositions, fat origin, age and/or species. Recent studies do not find HFD-induced increased levels of GFAP in the rat hippocampus (Raider et al, 2016; Ribeiro et al, 2018). In contrast, Tarantini et al found that mice exposed to a 60%-fat diet from 3 to 8 months of age show mild behavior deficits and neuroinflammation, which are exacerbated by exposure to a cellular stress induced by deletion of the transcription factor nrf2 that regulates the expression of antioxidant proteins, thus protecting against oxidative damage (Tarantini et al, 2018).…”
Section: Discussionmentioning
confidence: 88%